Analisis Materi Pembelajaran Aqidah Akhlak Dalam Penguatan Akhlak Siswa SMP IT Ibnu Halim - Iqbal M, Muhammad; Harfiani, Rizka (Yayasan Rahmat Islamiyah, 2024)
Learning aqidah morals is a subject that can explain faith and the formation of manners which can help shape students' character. This research was conducted to reveal how learning the Aqidah Akhlak shapes the morals of students and aims to analyze the learning of the Aqidah Akhlak in developing the morals of students at SMP IT Ibnu Halim. This research is research that uses a qualitative approach, because the approach is based on qualitative evidence, namely based on direct observation. This research uses data collection techniques that use data analysis through observation by looking and observing directly in the field.